Occupationally induced stress, strain and peak loads as related to age. - Ilmarinen, Juhani; Rutenfranz, Joseph (Scandinavian Journal of Work, Environment & Health, 1980)
From six different type of work 120 men, aged 23–60 a, were classified according to the Ergonomic Job Description Questionnaire into four groups representing specific work content (producing forces, coordinating motor and sensory functions, converting information into reactions, and producing information). Work stress was assessed with measurements of oxygen consumption (VO2) and with the registration of the minutes spent at different stress levels. Relative aerobic strain (RAS) was defined as the VO2 during work as the percentage of VO2max. Strain was measured with continuous recordings of heart rate during the workday. Peak loads were evaluated according to the relative number of minutes above the heart rate levels of 130, 150 and 170 beats/min. The VO2 during work was virtually identical in the age groups less than 35, 35–50 and greater than 50 a. The RAS tended to increase with age due to the decrease in VO2max. The strain remained practically the same in all the age groups. In the group ``coordinating motor and sensory functions'' strain tended to increase with age. Peak loads over 150 beats/min were not rare for the older subjects. The results suggest that stress and strain during work remain practically the same as age increases. The RAS, however, tends to increase with age within groups doing mainly physical work and with exposures to peak loads.
Keywords: age; heart rate; occupational stress; occupationally induced stress; oxygen consumption; peak load; relative aerobic strain; relative strain; strain; stress; work content